Enhancing Motivation and Innovation Leadership To Improve The Performance of The Indonesian National Police - Gananta, M.; Thalib, Prawitra; Suhariadi, Fendy; Rahmawati, Elvia; Hardaningtyas, Dwi (Global Writing Academica Researching & Publishing, 2024)
The rapid advancement of technology during the periods of the Industrial Revolution 4.0, Society 5.0, and Policing 5.0 has resulted in indistinct shifts that diverge from previously recognized patterns, thus necessitating innovative leadership approaches. A notable deficiency in self-motivation has contributed to subpar performance. As of 2016, a significant number of Indonesian National Police personnel were implicated in disciplinary infringements, breaches of ethical standards, and even criminal transgressions. Specifically, in that year, 6,662 cases of disciplinary infractions were recorded, with 2,772 subsequently addressed. Moreover, transgressions against the professional ethics of the Indonesian National Police saw an escalation from 1,041 cases in 2015 to 1,671 in 2016. The objective of the present research is to discern and evaluate the influences of motivational enhancement and innovative leadership on the performance of the Indonesian National Police. The study employs a qualitative paradigm, drawing insights from a case study-oriented literary analysis. It is discerned that in addressing internal shifts in the Indonesian National Police, there is an imperative to bolster motivation and cultivate innovative leadership in order to attain exceptional, efficacious, and competitive outcomes. Pioneering leaders deploy diverse strategies to guide and inspire their teams, fostering active participation and collaboration towards the realization of organizational goals and peak performance. Given the evolving dynamics within the Indonesian National Police, a leader's role transcends mere adaptation to external innovative trends; truly effective leaders position their institutions as benchmarks for peers. An implication of contemporary advancements is the emergence of more intricate criminal modalities, pressing the Indonesian National Police to evolve in tandem. Concurrent with the digital age, there has been a heightened national cognizance of the need to rectify disparities and rejuvenate standards, driving a transition towards a society that is dynamic, forward-thinking, and technologically proficient.